Feeding ecology and consumption rates of yellowfin tuna Thunnus albacares (Bonnaterre, 1788) in the eastern Arabian Sea - Varghese, Sijo P.; Somvanshi, V. S. (Indian Journal of Fisheries, 2016)
Diet composition, predator-prey relationships and consumption rates of yellowfin tuna Thunnus albacares in the western Indian Exclusive Economic Zone (eastern Arabian Sea) were studied by stomach content analysis. Stomachs of 406 specimens in the fork length range of 48 to 165.5 cm caught during exploratory longlining conducted in the eastern Arabian Sea during 2006 to 2009 were examined, of which, 15.52% were empty. Purple back flying squid (Sthenoteuthis oualaniensis) was thedominant prey species, followed by the swimming crab (Charybdis smithii), bigeye cigarfish (Cubiceps pauciradiatus) and flyingfishes (family Exocoetidae). Diet breadth index and the modified Costello diagram showed dominance of few prey species which are available in high densities in the Arabian Sea, indicating opportunistic feeding nature of this apex predator. Diet did not significantly differ between sexes and size groups. Higher food intake during premonsoon and winter monsoonindicated a seasonal variation in diet. A steady increase in the abundance of C. smithii and a decrease in the proportion of S. oualaniensis in the diet were observed from premonsoon to winter monsoon seasons. Yellowfin tuna in the Arabian Sea consume an average of 545.65 g of food in a day and require daily ration of 1.95% body weight per day.